Long Bone Metastasis in a Case of Medulloblastoma - Arare case report (BioMedical Research in Medicine (BMR Medicine) (ISSN 2349-0756), 2024)
We reported a case of medulloblastoma with upper end of tibia and lower end of femur metastasis. This was treated with CSI (craniospinal irradiation) two years back. After two year of follow-up he presented with pain over knee joint which was confirmed as metastasis to lower end of femur and upper end of tibia and then treated with palliative radiotherapy. Patient brain MRI shows thalamus mass suggestive of metastasis which was treated with palliative chemotherapy. Our case is unique in presentation because itpresented with long bone metastasis